Pengaruh Social Media Marketing terhadap Niat Beli ESQA Cosmetics Melalui Brand Trust - Ni Putu Wina Yustina Maharani; I Gusti Ayu Tirtayani; Komang Widhya Sedana Putra; Desak Made Febri Purnama (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
The local cosmetics industry in Indonesia continues to grow rapidly and has become increasingly popular among Generation Z. However, the boycott issue against ESQA Cosmetics, triggered by a controversy involving one of its founders, has led to a decline in consumer trust. This study aims to examine the influence of social media marketing on purchase intention through brand trust in the case of ESQA Cosmetics. The research was conducted in Bali using a quantitative approach with an explanatory research design. Data were collected through an online questionnaire involving 110 Generation Z respondents who had never purchased ESQA products but had interacted with ESQA’s official social media account (@esqacosmetics). Data analysis was performed using SmartPLS with mediation testing to examine the relationships among variables. The results indicate that social media marketing has a positive and significant effect on purchase intention through brand trust, suggesting that the effectiveness of social media strategies can strengthen brand trust and ultimately increase consumer purchase intention. This finding highlights that brand trust serves as a key psychological mechanism linking social media marketing to purchase behavior. The study recommends that ESQA Cosmetics enhance interaction and transparency in its social media communication, provide prompt responses to consumers, and emphasize the authenticity and benefits of its products to rebuild trust and strengthen purchase intention following the boycott issue.